The Effect of Human Resources Competency, Understanding of Government Accounting Standards, Internal Control Systems, Utilization of Information Technology on The Quality of Financial Statements Government of Bukittinggi City - Putri, Anne; Hadayanti, Mardiah; Siregar, Ahmad Zuhri (ADPEBI, 2024)
This study aims to determine the effect of human resource competence, understanding of government accounting standards, internal control systems, utilization of information technology on the quality of financial reports of the Bukittinggi City Government, both partially and simultaneously. This study is a quantitative study with primary data sources in the form of questionnaires. The population of this study were all employees in 28 Regional Government Work Units (SKPD) of the Bukittinggi City Government. Using purposive sampling, with the criteria of employees working in the finance department, who are directly involved in the preparation of financial reports: Head of Finance Sub-Division, Accounting Staff and Treasurer, Total samples obtained were 93 people. Data analysis used multiple linear regression with SPSS software version 20.00. The results of the study showed that simultaneously the variables of human resource competence, understanding of government accounting standards, internal control systems, utilization of information technology had an effect on the quality of financial reports. Partially the variable of human resource competence did not affect the quality of financial reports, while the variables of understanding of government accounting standards, internal control systems, utilization of information technology had an effect on the quality of financial reports.